PERANAN WANITA PEDAGANG SAYUR DI PASAR INDUK LAU CIH DALAM MENINGKATKAN PENDAPATAN KELUARGA - Juliana br Simbolon; Roida E. Sinaga; Robert Sinaga (JURNAL REGIONOMIC, 2020)
This study aims to determinate the role of a woman who sells vegetables in Induk Lau Cih market in improving family income. The research method used is qualitative in which this research intends to describe and interpreta condition. Among the research that was obtained were research results, long time the women who sell vegetables work in the market in a day, the age of a woman who sells vegetables in Induk market, family load of a woman who sells vegetables in Induk market, the daily wage of a vegetable trade in Induk market, income of husband of a woman who sells vegetables in Induk market and recent education of a woman who sells vegetables in Induk market. Based on the result of studies as described, Researchers came to the conclusiom that husband’s income is so low that it requires work.